Change of the scrape-off layer power width with the toroidal B-field direction in ASDEX upgrade. (22nd May 2015) - Faitsch, M; Sieglin, B; Eich, T; Sun, H J; Herrmann, A; ,
Abstract: The change of the scrape-off layer power width in dependence of the toroidal magnetic field direction is investigated in L-mode discharges in the upper single null (USN) configuration in ASDEX Upgrade. The heat flux onto the outer and inner divertor plates is measured using a fast 2D infrared camera. The heat flux distribution is described by an exponential power fall-off length and a diffusive broadening in the divertor region . In this paper the parameters, and, for the inner and outer divertor target are compared for both toroidal magnetic field directions. For the divertor broadening no dependence on the toroidal magnetic field direction is observed. The comparison between the near scrape-off layer electron temperature fall-off length and the power fall-off length are in agreement with the 2-point model. It is concluded that electron conduction is the main contribution for the scrape-off layer parallel transport in these discharges. The ratio between inner, , and outer, , power fall-off length is dependent on the toroidal magnetic field direction. The numerical values are for favourable ion drift direction and / for non-favourable drift direction. The different ratios are explained by vertical drifts, which are dependent on the toroidal magnetic field direction.